Silver sand flashing dry particles, glaze slip and preparation method of ceramic tile with silver sand decoration effect
By preparing silver sand flash dry particles and high-temperature matte dry particles, the components and ratios are optimized, and combined with the coloring and polishing process of the base glaze, the control difficulty and polishing problems of the metal texture tiles preparation process in the existing technology are solved, and the problem of the improvement of metal texture ceramic tiles is realized. The improvement of silver sand flash effect has increased the added value of the product.
Patent Information
- Application Number
- CN202411183756.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The existing preparation process of metal-textured ceramic tiles requires strict firing process and is difficult to control, resulting in low product quality and difficult to polish on the surface of the glaze layer, affecting the flash effect.
By preparing silver sand sparkling dry particles and high-temperature matte dry particles, optimize their components and ratios, combined with the base glaze addition and polishing process, the contrast between the base color and the silver sand sparkling dry particles can be increased, and the polishing of metal dry particles can be achieved. Effect.
The silver sand glitter effect is improved, the adaptation problem with high-temperature matte dry particles is solved, the silver sand decorative effect of ceramic tiles is achieved, and the added value of the product and market sales are enhanced.
Smart Images

Figure CN119191712A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic production, and in particular relates to a method for preparing silver sand flashing dry particles, glaze slurry and ceramic tiles with silver sand decorative effects. Background Art
[0002] From ancient times to the present, people have always preferred to use precious metals as decorative materials, such as the magnificent palaces and solemn temples. However, precious metals are rare and expensive, and ordinary people can hardly afford them. As a commonly used decorative material, ceramic tiles will undoubtedly greatly increase their added value and market sales if they can be given a metallic texture. The metallic texture ceramic tile products on the market mainly include golden yellow, silver white, copper green and iron black. The preparation process of these products usually adds an excess of metal oxides to the glaze formula, and the metallic texture is achieved by precipitating metal crystals on the glaze during the firing process. However, this preparation process has very strict requirements on the firing process, and there are certain control difficulties in the production process, resulting in a low rate of product excellence. In addition, since the metal crystals are precipitated on the surface of the glaze layer, it is difficult to polish and brighten the product, which affects the flashing effect of the metallic texture. Summary of the invention
[0003] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing silver sand flash dry particles, glaze slurry, and ceramic tiles with silver sand decorative effects, wherein a large amount of iron oxide, an appropriate amount of quartz, and an optimized firing process are introduced in the preparation of the silver sand flash dry particles. The formula composition of the silver sand flash dry particles directly affects the metal flash effect of the product. In addition to satisfying the silver sand flash effect, the problem of matching with high-temperature matte dry particles, bottom glaze, etc. is also solved. The ceramic tiles of the present invention prepare silver sand flash dry particles and high-temperature matte dry particles, adjust and optimize their components and proportions, and increase the contrast between the base color and the silver sand flash dry particles by adding color to the bottom glaze, lowering the luminosity of the dry particles, and at the same time, realize that the metal dry particles can be polished, thereby achieving the purpose of enhancing the silver sand flash effect.
[0004] To solve the above problems, the present invention is implemented through the following technical solutions:
[0005] The first invention object of the present invention is:
[0006] Provided is a method for preparing silver sand flash dry particles, which comprises the following components in weight percentage:
[0007] Iron oxide 80-96%, quartz 3-8%, talc 1-3%, titanium oxide 0.2-0.6%, aluminum oxide 0.1-2%; the sum of all components is 100%;
[0008] The raw material components are weighed according to the formula ratio, mixed evenly, melted at 1600°C, kept warm for 5 to 8 hours, and then slowly cooled to room temperature at a cooling rate of 8 to 25°C / h to precipitate metal α-Fe2O3 crystals, crushed, and screened to obtain 20 to 40 mesh dry particles to prepare silver sand flash dry particles.
[0009] The preparation method of the silver sand flash dry granules of the present invention is further optimized as follows:
[0010] The chemical composition of the silver sand dry particles is: SiO2 3-5%, Al2O3 0.5-2%, Fe2O3 90-96%, CaO0.1-0.8%, MgO 0.3-0.9%, K2O 0-0.2%, Na2O 0-0.2%, TiO2 0.1-0.6%, and ignition loss 0-0.8%; the sum of all the components is 100%.
[0011] The second object of the present invention is:
[0012] Provided is a method for preparing a silver sand flash dry granule glaze slurry, which comprises the following components in parts by weight:
[0013] 100 parts of glue suspension, 15-50 parts of the aforementioned silver sand flash dry particles, 10-30 parts of high temperature matte dry particles;
[0014] Weigh the raw material components according to the formula ratio, stir them evenly, and age them for 2 to 6 hours to prepare the silver sand flash dry granule glaze slurry;
[0015] The high-temperature matte dry particles include the following components in weight percentage:
[0016] Potassium feldspar 50-60%, talc 5-10%, calcite 7-15%, barium carbonate 5-10%, wollastonite 5-10%, zinc oxide 3-5%, aluminum oxide 3-7%; the sum of all components is 100%;
[0017] According to the formula of high-temperature matte dry particles, corresponding raw material components are selected, mixed evenly by dry mixing, melted at 1600°C, quenched with water, dried, crushed, and iron is sieved to prepare high-temperature matte dry particles with a particle size of 40 to 150 meshes.
[0018] The preparation method of the silver sand flash dry granule glaze slurry of the present invention is further optimized as follows:
[0019] The chemical composition of the high-temperature matte dry particles is: SiO2 59-65%, Al2O3 18-22%, Fe2O3 0.1-0.7%, CaO 10-11%, MgO 0.8-3%, K2O 3.5-5.5%, Na2O 0.8-1.5%, TiO2 0-0.1%, BaO 3-7%, ZnO 3-5%, ignition loss 0-0.1%; the sum of all the components is 100%.
[0020] The third invention object of the present invention is:
[0021] Provided is a method for preparing a ceramic tile with a silver sand decorative effect, comprising the following preparation steps:
[0022] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0023] S2. Printing an inkjet pattern onto the brick body A to obtain a brick body B;
[0024] S3. Apply the aforementioned silver sand flash dry granule glaze slurry to the brick body B to obtain a brick body C;
[0025] S4. The brick body C is fired at high temperature to obtain a brick body D;
[0026] S5. The brick body D is subjected to brushing, polishing and sorting to obtain a ceramic brick with a silver sand decorative effect.
[0027] The preparation method of the ceramic tile with silver sand decorative effect of the present invention is further optimized as follows:
[0028] The base glaze described in step S1 includes the following components in weight percentage:
[0029] Potassium feldspar 40-60%, kaolin 5-10%, alumina 12%-18%, zirconium silicate 5-15%, quartz 10-30%, talc 2-5%; the sum of all components is 100%;
[0030] Add 1.0% to 1.5% by weight of auxiliary raw materials and 0.5% to 10% by weight of glaze colorants;
[0031] The auxiliary raw materials include sodium tripolyphosphate and methyl cellulose;
[0032] The glaze colorant includes a mixture of one or more of cobalt black, package red, package yellow, cobalt blue, etc.;
[0033] The weight percentage chemical composition of the base glaze is:
[0034] SiO2 53~65%, Al2O3 18~27%, Fe2O3 0.1~0.5%, CaO 0.1~0.8%, MgO0.1~0.9%, K2O 2.8~3.9%, Na2O 1.2~2.1%, TiO2 0~0.1%, ZrO2 4~12%, loss on ignition 0~0.8%, the sum of all components is 100%.
[0035] The preparation method of the ceramic tile with silver sand decorative effect of the present invention is further optimized as follows:
[0036] The specific gravity of the glaze slurry of the bottom glaze in step S1 is 1.85-1.95 g / ml, the flow rate is 30-60 seconds (100 ml volt cup), and the glaze amount of the bottom glaze is 400-700 g / m 2 .
[0037] The preparation method of the ceramic tile with silver sand decorative effect of the present invention is further optimized as follows:
[0038] The specific gravity of the silver sand flash dry granule glaze slurry described in step S3 is 1.15-1.55 g / ml, the flow rate is 40-80 seconds (100 ml volt cup), and the glazing amount of the silver sand flash dry granule glaze slurry is 200-600 g / m 2 .
[0039] The preparation method of the ceramic tile with silver sand decorative effect of the present invention is further optimized as follows:
[0040] The high temperature firing time in step S4 is 45 to 60 minutes, and the firing temperature is 1150°C to 1180°C.
[0041] The preparation method of the ceramic tile with silver sand decorative effect of the present invention is further optimized as follows:
[0042] The brush polishing described in step S5 is to use an elastic grinding block, a matte module, and a carbon fiber grinding block as polishing tools to perform polishing treatment in sequence, and the brightness after polishing is 7 to 15 degrees;
[0043] The main component of the elastic grinding block is resin-bonded diamond abrasive;
[0044] The main components of the matte module are resin-bonded silicon carbide and magnesium oxide abrasives;
[0045] The main components of the carbon fiber grinding block are a combination of ultrafine silicon carbide abrasive and carbon fiber.
[0046] The technical solution of the present invention is to prepare silver sand flash dry particles and high temperature matte dry particles in advance, and to prepare silver sand dry particle glaze slurry by mixing the silver sand flash dry particles and the high temperature matte dry particles in a certain ratio; after high temperature firing, a polishing process is performed to obtain a tile product with a silver sand dry particle decorative effect.
[0047] The present invention focuses on the research of key technologies in the following aspects:
[0048] (I) Preparation of silver sand flash dry particles:
[0049] The formula composition of silver sand glitter dry particles directly affects the metallic glitter effect of the product. For silver sand glitter dry particles, in addition to having silver sand glitter effects, they also need to meet the requirements of being compatible with matte dry particles, base glaze, etc.
[0050] In order to obtain silver sand flash dry particles that meet production needs, the present invention adjusts and optimizes them from the following aspects.
[0051] (1) Introducing a large amount of iron oxide:
[0052] The preparation of the silver sand flash dry particles in the present invention is mainly through the high temperature sintering, the Fe element is enriched in large quantities, and α-Fe2O3 is supersaturated and precipitated. Since the arrangement of α-Fe2O3 has good orientation, when the physical coloring generated by the structural arrangement plays a leading role, Fe 3+ The chemical coloring is suppressed, and the color appears silvery white in the macroscopic view, rather than the original iron red or rust color. Therefore, the amount of iron oxide added in the formula has a crucial influence on the crystallization of α-Fe2O3. The present invention achieves the purpose of promoting the crystallization of iron oxide by adding a large amount of iron oxide (80-96%) in the formula to make the iron content in a saturated state.
[0053] (2) Introduce appropriate amount of quartz:
[0054] Since a large amount of iron oxide is added to the formula of the silver sand flash dry particles, in order to solve the compatibility problem between the silver sand flash dry particles and the matte dry particles, the present invention introduces an appropriate amount of quartz into the formula of the silver sand flash dry particles. Quartz is a commonly used raw material for ceramic glazes. The addition of quartz effectively solves the problem of combining the silver sand flash dry particles with the matte dry particles.
[0055] (3) Optimization of firing process:
[0056] Different from the melting and quenching process of ordinary fired frit dry particles, since silver sand flash dry particles need to precipitate α-Fe2O3 crystals, the crystallization process requires energy and time for crystal growth. Drawing on the firing process of ancient porcelain iron-based crystalline glaze, after many experiments and summaries, the well-mixed raw materials are placed in a furnace, melted at 1600℃, kept warm for 5 to 8 hours, and then slowly cooled to room temperature at a cooling rate of 8 to 25℃ / h to precipitate α-Fe2O3 crystals. After crushing and screening, silver sand flash dry particles are obtained.
[0057] (4) Optimization of the particle size of silver sand flash dry particles:
[0058] The particle size of silver sand flash dry particles has a great influence on the flash effect of the glaze surface. The finer the particles, the worse the flash effect. However, when the silver sand flash particles are coarse, the glaze curtain is easy to split when pouring the glaze, and the glaze surface is also rough, which is difficult to produce.
[0059] The invention crushes the fired silver sand flash dry particles and screens the fineness, and screens 4-6 meshes, 20-40 meshes and 60-100 meshes respectively.
[0060] Table 1 Effect of the fineness of silver sand flash dry particles on the glaze effect
[0061]
[0062] Through experimental comparison, it is found that when the fineness of the silver sand flash dry particles is 20-40 meshes, the glaze effect is optimal. Therefore, in the preparation process of the present invention, the fired silver sand flash dry particles are crushed and the silver sand flash dry particles of 20-40 meshes are screened out for use.
[0063] (II) Preparation of high temperature matte dry granules:
[0064] In order to further highlight the glittering effect of silver sand, the present invention reduces the glossiness of the glaze dry particles, and uses a low-gloss matte dry particle surface to better bring out the glittering effect of silver sand.
[0065] In order to obtain high-temperature matte dry granules that meet production needs, the present invention adjusts and optimizes the existing matte dry granule formula from the following aspects:
[0066] (1) Introducing alumina powder:
[0067] The role of alumina (Al2O3) in glaze is to form a network intermediate. It has a high melting point and stable chemical properties. By introducing alumina, the melting temperature of the dry particles can be significantly increased and the brightness of the dry particles can be reduced. The higher melting temperature can prevent the silver sand flash dry particles from reacting with the high-temperature matte dry particles during the high-temperature firing process, thereby affecting the glaze and the flash effect.
[0068] (2) Introducing appropriate amounts of calcium oxide, barium oxide, and magnesium oxide:
[0069] Calcium oxide, barium oxide, and magnesium oxide are mainly used as flux in glazes, which reduce the melting temperature of dry particles and improve the chemical stability and anti-fouling performance of the glaze. Compared with K2O and Na2O, their melting range is wider. At the same time, at high temperatures, calcium oxide, barium oxide, and magnesium oxide react with Al and Si to form microcrystals, thereby reducing the brightness of dry particles. In addition, microcrystals can also enhance the hardness and corrosion resistance of the glaze.
[0070] (III) Optimization of polishing process:
[0071] The existing glaze polishing process usually has three steps: rough grinding, fine grinding and fine grinding. The glaze gloss of the produced polished glaze tiles is very high, but it cannot reach the brightness required for the flash of silver sand dry particles. The traditional soft polishing technology usually removes the fine grinding step to reduce the gloss of the glaze, but after polishing, the glaze of the tile is severely scratched and the brightness is uneven. Therefore, in order to obtain silver sand products with good flash effect, the present invention makes improvements in the polishing process.
[0072] After research, the following three polishing abrasives were used in this project:
[0073] (1) Using elastic abrasive blocks as polishing tools, the abrasive block is mainly composed of resin-bonded diamond abrasives;
[0074] (2) A matte module is used as a polishing tool, and the main components of the grinding block are resin-bonded silicon carbide and magnesium oxide abrasives;
[0075] (3) Use carbon fiber grinding blocks as polishing tools. The components of carbon fiber grinding blocks are mainly a combination of ultrafine silicon carbide abrasives and carbon fibers.
[0076] The product is polished in sequence by the above three types of abrasive tools, and the obtained product has a uniform and moderate glossiness (7 to 15 degrees), a smooth feel, and a strong silver sand flash effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is a real picture of the ceramic tile with silver sand decorative effect prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0078] In order to make the application, technical scheme and advantages of the present invention more clear, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the embodiments are only used to illustrate the present invention, but not to limit the protection scope of the present invention. All simple improvements to the preparation method of the present invention under the premise of the concept of the present invention belong to the protection scope of the present invention.
[0079] Example 1
[0080] A method for preparing a ceramic tile with a silver sand decorative effect, comprising the following preparation steps:
[0081] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0082] S2. Printing an inkjet pattern onto the brick body A to obtain a brick body B;
[0083] S3. Applying silver sand flash dry granule glaze slurry to the brick body B to obtain a brick body C;
[0084] S4. The brick body C is fired at high temperature to obtain a brick body D;
[0085] S5. The brick body D is subjected to brushing, polishing and sorting to obtain a ceramic brick with a silver sand decorative effect.
[0086] The base glaze described in step S1 includes the following components in weight percentage:
[0087] Potassium feldspar 52%, kaolin 8%, alumina 14%, zirconium silicate 7%, quartz 15%, talc 4%;
[0088] Add 1.2% by weight of auxiliary raw materials and 3% of glaze black material;
[0089] The auxiliary raw materials include sodium tripolyphosphate and methyl cellulose.
[0090] The specific gravity of the base glaze slurry is 1.88g / ml, the flow rate is 38 seconds (100ml volt cup), and the base glaze application amount is 490g / m 2 .
[0091] The silver sand flash dry granule glaze slurry described in step S3 comprises the following components in parts by weight:
[0092] 100 parts of glue suspension, 23 parts of silver sand flash dry particles, 15 parts of high temperature matte dry particles;
[0093] Weigh the raw material components according to the formula ratio, stir them evenly, and age them for 2 to 6 hours to prepare the silver sand flash dry granule glaze slurry;
[0094] The specific gravity of the silver sand flash dry granule glaze slurry is 1.42g / ml, the flow rate is 56 seconds (100ml volt cup), and the glaze amount of the silver sand flash dry granule glaze slurry is 320g / m 2 .
[0095] The silver sand flash dry particles include the following components in weight percentage:
[0096] Iron oxide 94%, quartz 3.3%, magnesia 1.2%, nano titanium oxide 0.3%, aluminum oxide 1.2%;
[0097] The raw material components are weighed according to the formula ratio, mixed evenly, melted at 1600°C, kept warm for 6 hours, and then cooled to room temperature at a cooling rate of 15°C / h to precipitate metal α-Fe2O3 crystals, which are crushed and screened into 20-40 mesh dry particles to prepare silver sand flash dry particles.
[0098] The high-temperature matte dry particles include the following components in weight percentage:
[0099] Potassium feldspar 58%, talc 7%, calcite 10%, barium carbonate 8%, wollastonite 8%, zinc oxide 4%, aluminum oxide 5%;
[0100] According to the formula of high-temperature matte dry particles, corresponding raw material components are selected, mixed evenly by dry mixing, melted at 1600°C, quenched with water, dried, crushed, and iron is sieved to prepare high-temperature matte dry particles with a particle size of 40 to 150 meshes.
[0101] The high temperature firing time in step S4 is 55 minutes, and the firing temperature is 1163°C.
[0102] The brush polishing described in step S5 is preferably performed by using an elastic grinding block, a matte module, and a carbon fiber grinding block as polishing tools to perform polishing treatment in sequence, and the brightness after polishing is 7 to 15 degrees.
[0103] Example 2
[0104] A method for preparing a ceramic tile with a silver sand decorative effect, comprising the following preparation steps:
[0105] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0106] S2. Printing an inkjet pattern onto the brick body A to obtain a brick body B;
[0107] S3. Applying silver sand flash dry granule glaze slurry to the brick body B to obtain a brick body C;
[0108] S4. The brick body C is fired at high temperature to obtain a brick body D;
[0109] S5. The brick body D is subjected to brushing, polishing and sorting to obtain a ceramic brick with a silver sand decorative effect.
[0110] The base glaze described in step S1 includes the following components in weight percentage:
[0111] Potassium feldspar 42%, kaolin 8%, alumina 10%, zirconium silicate 12%, quartz 23%, talc 5%;
[0112] Add 1% by weight of auxiliary raw materials and 6% of glaze black material;
[0113] The auxiliary raw materials include sodium tripolyphosphate and methyl cellulose.
[0114] The specific gravity of the base glaze slurry is 1.92g / ml, the flow rate is 35 seconds (100ml volt cup), and the base glaze application amount is 560g / m 2 .
[0115] The silver sand flash dry granule glaze slurry described in step S3 comprises the following components in parts by weight:
[0116] 100 parts of glue suspension, 45 parts of silver sand flash dry particles, 20 parts of high temperature matte dry particles;
[0117] Weigh the raw material components according to the formula ratio, stir them evenly, and age them for 2 to 6 hours to prepare the silver sand flash dry granule glaze slurry;
[0118] The specific gravity of the silver sand flash dry granule glaze slurry is 1.5g / ml, the flow rate is 50 seconds (100ml volt cup), and the glazing amount of the silver sand flash dry granule glaze slurry is 400g / m 2 .
[0119] The silver sand flash dry particles include the following components in weight percentage:
[0120] Iron oxide 94%, quartz 3.3%, talc 1.2%, titanium oxide 0.3%, aluminum oxide 1.2%;
[0121] The raw material components are weighed according to the formula ratio, mixed evenly, melted at 1600°C, kept warm for 6.5 hours, and then cooled to room temperature at a cooling rate of 22°C / h to precipitate metal α-Fe2O3 crystals, which are crushed and screened into 20-40 mesh dry particles to prepare silver sand flash dry particles.
[0122] The high-temperature matte dry particles include the following components in weight percentage:
[0123] Potassium feldspar 58%, talc 7%, calcite 10%, barium carbonate 8%, wollastonite 8%, zinc oxide 4%, aluminum oxide 5%;
[0124] According to the formula of high-temperature matte dry particles, corresponding raw material components are selected, mixed evenly by dry mixing, melted at 1600°C, quenched with water, dried, crushed, and iron is sieved to prepare high-temperature matte dry particles with a particle size of 40 to 150 meshes.
[0125] The high temperature firing time in step S4 is 50 minutes, and the firing temperature is 1160°C.
[0126] The brush polishing described in step S5 is preferably performed by using an elastic grinding block, a matte module, and a carbon fiber grinding block as polishing tools to perform polishing treatment in sequence, and the brightness after polishing is 7 to 15 degrees.
[0127] Comparative Examples 1 to 3 are prepared in the same manner as Example 1, with the main difference being the selection of some raw materials. The specific raw material differences and glaze effects are detailed in Table 2.
[0128] Table 2 Comparison of glaze effects between the embodiment and the comparative example
[0129] project Addition of Flash Dry Granules Addition of matte dry particles Glaze effect Example 1 Silver sand flash dry granules High temperature matte dry granules The glaze is smooth and the silver sand flash effect is obvious Example 2 Silver sand flash dry granules High temperature matte dry granules The glaze is smooth and the silver sand flash effect is obvious Comparative Example 1 Ordinary flash dry particles High temperature matte dry granules The glaze is smooth, without silver sand glitter effect Comparative Example 2 Silver sand flash dry granules Bright dry granules Strong light perception, weak silver sand flash effect Comparative Example 3 Ordinary flash dry particles Bright dry granules The glaze is smooth, without silver sand glitter effect
[0130] The ceramic tile of the present invention prepares silver sand flash dry particles and high temperature matte dry particles, adjusts and optimizes their components and proportions, and increases the contrast between the base color and the silver sand flash dry particles by adding color to the base glaze and lowering the brightness of the dry particles. At the same time, the metal dry particles can be polished, thereby achieving the purpose of enhancing the silver sand flash effect. Therefore, the adaptation of the silver sand flash dry particles and the high temperature matte dry particles is very important.
[0131] In Comparative Example 1, ordinary glitter dry particles were used, resulting in the glaze surface having no silver sand glitter effect;
[0132] In Comparative Example 2, due to the use of bright dry particles, the glaze has a stronger sense of light, thereby weakening the silver sand glitter.
[0133] In Comparative Example 3, ordinary glitter dry particles and bright dry particles were used, which also resulted in the glaze having no glitter effect.
[0134] To sum up, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
[0135] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0136] The experimental methods without specific conditions in the present invention are usually carried out under conventional conditions or conditions recommended by the manufacturer.
[0137] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.
[0138] Unless otherwise indicated, percentages and parts are by weight.
[0139] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.
[0140] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.
Claims
1. A method for preparing silver sand flash dry particles, characterized in that: It includes the following components in weight percentage: Iron oxide 80-96%, quartz 3-8%, talc 1-3%, titanium oxide 0.2-0.6%, aluminum oxide 0.1-2%; the sum of all components is 100%; The raw material components are weighed according to the formula ratio, mixed evenly, melted at 1600°C, kept warm for 5 to 8 hours, and then slowly cooled to room temperature at a cooling rate of 8 to 25°C / h to precipitate metal α-Fe2O3 crystals, crushed, and screened to obtain 20 to 40 mesh dry particles to prepare silver sand flash dry particles.
2. The method for preparing the silver sand flash dry granules according to claim 1, characterized in that: The chemical composition of the silver sand dry particles is: SiO2 3-5%, Al2O3 0.5-2%, Fe2O3 90-96%, CaO 0.1-0.8%, MgO 0.3-0.9%, K2O 0-0.2%, Na2O 0-0.2%, TiO2 0.1-0.6%, and ignition loss 0-0.8%; the sum of all the components is 100%.
3. A method for preparing a silver sand flash dry granule glaze slurry, characterized in that: It includes the following components by weight: 100 parts of glue suspension, 15-50 parts of silver sand flash dry particles according to claim 1, and 10-30 parts of high temperature matte dry particles; Weigh the raw material components according to the formula ratio, stir them evenly, and age them for 2 to 6 hours to prepare the silver sand flash dry granule glaze slurry; The high-temperature matte dry particles include the following components in weight percentage: Potassium feldspar 50-60%, talc 5-10%, calcite 7-15%, barium carbonate 5-10%, wollastonite 5-10%, zinc oxide 3-5%, aluminum oxide 3-7%; the sum of all components is 100%; According to the formula of high-temperature matte dry particles, corresponding raw material components are selected, mixed evenly by dry mixing, melted at 1600°C, quenched with water, dried, crushed, and iron is sieved to prepare high-temperature matte dry particles with a particle size of 40 to 150 meshes.
4. The method for preparing the silver sand flash dry granule glaze slurry according to claim 3, characterized in that: The chemical composition of the high-temperature matte dry particles is: SiO2 59-65%, Al2O3 18-22%, Fe2O3 0.1-0.7%, CaO 10-11%, MgO 0.8-3%, K2O 3.5-5.5%, Na2O 0.8-1.5%, TiO2 0-0.1%, BaO 3-7%, ZnO 3-5%, ignition loss 0-0.1%; the sum of all the components is 100%.
5. A method for preparing a ceramic tile with silver sand decorative effect, characterized in that: It comprises the following preparation steps: S1. preparing a body and applying a base glaze to the body to obtain a brick body A; S2. Printing an inkjet pattern onto the brick body A to obtain a brick body B; S3. Applying the silver sand flash dry granule glaze slurry according to claim 3 to the brick body B to obtain a brick body C; S4. The brick body C is fired at high temperature to obtain a brick body D; S5. The brick body D is subjected to brushing, polishing and sorting to obtain a ceramic brick with a silver sand decorative effect.
6. The method for preparing a ceramic tile with silver sand decorative effect according to claim 5, characterized in that: The base glaze described in step S1 includes the following components in weight percentage: Potassium feldspar 40-60%, kaolin 5-10%, alumina 12%-18%, zirconium silicate 5-15%, quartz 10-30%, talc 2-5%; the sum of all components is 100%; Add 1.0% to 1.5% by weight of auxiliary raw materials and 0.5% to 10% by weight of glaze colorants; The auxiliary raw materials include sodium tripolyphosphate and methyl cellulose; The glaze colorant includes a mixture of one or more of cobalt black, package red, package yellow, cobalt blue, etc.; The weight percentage chemical composition of the base glaze is: SiO2 53~65%, Al2O3 18~27%, Fe2O3 0.1~0.5%, CaO 0.1~0.8%, MgO0.1~0.9%, K2O 2.8~3.9%, Na2O 1.2~2.1%, TiO2 0~0.1%, ZrO2 4~12%, loss on ignition 0~0.8%, the sum of all components is 100%.
7. The method for preparing a ceramic tile with silver sand decorative effect according to claim 5, characterized in that: The specific gravity of the glaze slurry of the bottom glaze in step S1 is 1.85-1.95 g / ml, the flow rate is 30-60 seconds, and the glaze amount of the bottom glaze is 400-700 g / m 2 .
8. The method for preparing a ceramic tile with silver sand decorative effect according to claim 5, characterized in that: The specific gravity of the silver sand flash dry granule glaze slurry in step S3 is 1.15-1.55 g / ml, the flow rate is 40-80 seconds, and the glaze application amount of the silver sand flash dry granule glaze slurry is 200-600 g / m 2 .
9. The method for preparing a ceramic tile with silver sand decorative effect according to claim 5, characterized in that: The high temperature firing time in step S4 is 45 to 60 minutes, and the firing temperature is 1150°C to 1180°C.
10. The method for preparing a ceramic tile with silver sand decorative effect according to claim 5, characterized in that: The brush polishing described in step S5 is to use an elastic grinding block, a matte module, and a carbon fiber grinding block as polishing tools to perform polishing treatment in sequence, and the brightness after polishing is 7 to 15 degrees; The main component of the elastic grinding block is resin-bonded diamond abrasive; The main components of the matte module are resin-bonded silicon carbide and magnesium oxide abrasives; The main components of the carbon fiber grinding block are a combination of ultrafine silicon carbide abrasive and carbon fiber.
Citation Information
Patent Citations
Wear-resistant ceramic tile with diamond-like luster effect and preparation method of wear-resistant ceramic tile
CN110304945A
Ceramic pigment and application thereof
CN111961354A
Aventurine glaze ceramic tile and preparation method thereof
CN113402305A
Matte dry granular material and preparation method thereof
CN113860737A
Silver glaze and preparation method for firing silver glaze in reducing atmosphere
CN115838246A
Cited By
Ceramic tile surface metal point decoration mixed spraying device
CN224834299U
